The Impact of Development Finance Institutions on Economic Growth: A case of South Africa - Zikhali, Chester N (Graduate School of Business (GSB), 2022)
The relationship between financial development and economic growth remains a crucial subject of exploration in the academic world. Although several therioes and studies have been conducted to assess casuality between these two economic indicator proxies, the results remain inconclusive as to whether financial development causes economic growth or the opposite is true. Furthermore, the link between development finance institutions and economic growth is yet to receive empirical examination in emerging markets such as South Africa. Since the emancipation of South African country from apartheid the government embarked on several strategies to boost economic growth, one of which is the outlay of funds from the fiscus to development finance institutions to boost capital formation, which in turn results in growth. Whether or not these institutions and the extensions they make results in economic growth is subject to research. This study explores the long and short run effect of development finance institutions extensions on economic growth in South Africa from 1995 to 2018. It utilises annual aggregated development finance institutions extensions and real GDP as proxies for DFIs development and economic growth respectively. The study employs the autoregressive distributed lag (ARDL) bounds tests approach to co-integration developed by (M. Hashem Pesaran, Shin, & Smith, 2001) to determine the relationship between development finance committments development and economic growth, along with Augmented Dickey-Fuller tests and Philip Perron tests to test for unit roots on the data. The data was obtained from SADC statistics, World Bank, South African Reserve Bank, Open Source Capital and OECD library. The results of the study found evidence to support a deterministic relationship between the DFIs development and economic growth after controlling for trade openness and stock market development. The long run effect of DFI_E on economic growth revealed that DFIs extensions show significant influence on economic growth in South Africa. It therefore recommendeds that South Africa's policy makers should focus on policies that allow proliferation and ease of capital movements for international DFIs in the country. Additionally, the study recommends that the South African government increase its funding to domestic DFIs from the fiscus to enhance economic growth.